IFNα Inducible Models of Murine SLE - Davidson, Anne; Liu, Zheng (Frontiers in Immunology, 2013)
The role of type I interferons (IFNs) in SLE pathogenesis has been a subject of intense investigation in the last decade. The strong link between type I IFNs and SLE was initially provided by ex vivo studies showing that exposure of peripheral blood mononuclear cells to immune complexes from SLE patients elicits a signature of IFN inducible genes and was then further highlighted by human genetic studies. The mechanisms by which type I IFNs, especially IFN alpha (IFN-α), modulate the immune system and exacerbate SLE have been largely elucidated through studies in mouse lupus models. In this review, we discuss the characteristics of several such models in which disease is accelerated by ectopically expressed IFN-α. We also summarize several studies which tested therapeutic interventions in these models and discuss the advantages and disadvantages of using IFN-α accelerated models to study experimental treatments for lupus.